ANALISIS PENERAPAN SOFTWARE ACCURATE PADA SIKLUS PEMBELIAN BARANG DI PT. SARANA NIKOTEKNIK - Oktaviani, Mellyna; Chitra Santi (Journal of Innovation Research and Knowledge, 2023)
PT. Sarana Nikoteknik problems are as follows: the process of recording data for purchase is less efficient because the letter request of goods is recorded manually and order orders still use Excel; the existence of stock differences or stock differences that occur on the old program because the data must always be updated by replacing data; the stock difference also occurs due to the presence of more than one master name; and the input of the number of the report of accep. The purpose of this research is to learn about and evaluate the benefits of using accurate software. Data analysis is performed by comparing the results of the precise software implementation to the preceding process using desktop tools. According to the findings of the research, the use of software to the goods purchasing cycle at PT. Sarana Nikoteknik delivers a number of major benefits. Among them include increased administrative efficiency in entering purchase data, easier tracking of purchase reports, reduced data input mistakes, and the production of accurate and timely reports.